Respiratory function in vocal soloists, opera singers and wind instrument musicians - Ksinopoulou, Helen; Hatzoglou, Chryssa; Daniil, Zoe; Gourgoulianis, Konstantinos; Karetsi, Helen (La Medicina del Lavoro, 2016)
Introduction: Current studies have not yet reached a definitive conclusion on the effects of singing and playing wind instruments professionally on an individual’s respiratory function. Objective: The purpose of this study was to investigate the respiratory function of wind instrument players and opera singers in comparison with a group of healthy individuals. Methods: The experimental group comprised 45 men and 35 women, 58 opera singers and vocal soloists in total and 22 wind instruments players. Eighty controls were all non-smokers, healthy individuals, matched for age and sex. Spirometry was performed with a dry spirometer, according to the American Thoracic Society recommendations. Results: The mean age of the experimental group was 47.9 (15.5) years for men and 46.6 (16.8) for women. Experimental group and controls differed (p<0.01) in FVC [%predicted values: 98.69±13.07 vs 89.62±14.01 (men), 104.2±17.7 vs 93.8±13.9 (women)], FEV1[% predicted values: 98.69±13.07 vs 89.62±14.01 (men), 104.2±17.7 vs 93.8±13.9 (women)] and in PEFR values (p=0.001). [100.4±18.8 vs 76.7±19.8 (men)]. FEV1/FVC ratio significant differences were detected only in women (p=0.001, for predicted values). Conclusion: The findings of the present study provide evidence that professional involvement with wind musical instrument or monody might have beneficial effects on respiratory function. Future therapeutic perspectives, and associations between a documented improved respiratory function and performance by the musician should be examined.